PENGEMBANGAN PERANGKAT PEMBELAJARAN MATERI PERSEGI DAN PERSEGI PANJANG MENGGUNAKAN STRATEGI REACT - Maiviyani, Maiviyani; Laurens, Theresia; Matitaputty, Christi (JUPITEK : Jurnal Pendidikan Matematika, 2018)
Education in the present has become a necessity, the need for knowledge gained through the learning process both in school and learning from the environment of residence. Mathematical skills are important for everyday life, when students work in activities that are based on everyday life situations; they see ways of applying the mathematical skills they are learning to the real world. Thelearning strategy REACT is one of the learning strategies that use the environment as a source of learning. Besides the teaching learning process with active student learning methods (CBSA) the teacher must be more active in preparing lesson material, planning the process to be carried out such as RPP, preparing evaluation such as LKS and follow-up. From the results of the study the development of learning tools for student activities reached 91.25% and the success rate of students reached 70%. Thus the development of a square and rectangular learning device using theREACTstrategy has a good effect on student activity and student learning outcomes